2020
DOI: 10.1186/s12935-020-1101-x
|View full text |Cite
|
Sign up to set email alerts
|

EphA5 knockdown enhances the invasion and migration ability of esophageal squamous cell carcinoma via epithelial-mesenchymal transition through activating Wnt/β-catenin pathway

Abstract: Background: The erythropoietin-producing hepatocellular (Eph) receptor A5 (EphA5) has been found to be overexpressed in some malignant tumors and is associated with disease prognosis. However, the role of EphA5 in esophageal squamous cell carcinoma (ESCC) is not clear. Methods: In the present study, we measured the expression of EphA5 in ESCC tissues and cell lines including KYSE150 and KYSE450 cells. siRNA transfection was used to interfere with EphA5 expression in ESCC cell lines. Cell viability, colony form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…The high expression of circRNA-000911 could antagonize miR-449a, thereby increasing Notch1 expression to inhibit cell proliferation, migration, and invasion and to promote apoptosis of breast cancer cells. Lu H. et al ( 2020 ) found that CIRS-126 regulated the expression of programmed cell death protein 4 (PDCD4) and inhibited the proliferation of ovarian granulosa cells by acting as a miR-21 sponge in polycystic ovary syndrome. In summary, circRNA–miRNA–messenger RNA (mRNA) regulatory network plays an important role in the occurrence and development of gynecologic diseases, while circRNA has different targets and functions in different tissue cells.…”
Section: Introductionmentioning
confidence: 99%
“…The high expression of circRNA-000911 could antagonize miR-449a, thereby increasing Notch1 expression to inhibit cell proliferation, migration, and invasion and to promote apoptosis of breast cancer cells. Lu H. et al ( 2020 ) found that CIRS-126 regulated the expression of programmed cell death protein 4 (PDCD4) and inhibited the proliferation of ovarian granulosa cells by acting as a miR-21 sponge in polycystic ovary syndrome. In summary, circRNA–miRNA–messenger RNA (mRNA) regulatory network plays an important role in the occurrence and development of gynecologic diseases, while circRNA has different targets and functions in different tissue cells.…”
Section: Introductionmentioning
confidence: 99%
“…The cell viability and invasion and migration ability of esophageal cancer cells were accelerated after EPHA5 knockdown by siRNA. More recently, the roles of the EPHA5 receptor in lung cancer have been focused on [18,20,23,24]. EPHA5 expression was checked in lung cancer cell lines and human non-small cell lung cancer TMA (tissue microarray) specimens [18].…”
Section: Discussionmentioning
confidence: 99%
“…EPHA5 mRNA and protein expression were measured in esophageal squamous cell carcinoma cell lines and tissues. High expression of EPHA5 was found in esophageal squamous cell carcinoma tissues and cell lines [23]. The cell viability and invasion and migration ability of esophageal cancer cells were accelerated after EPHA5 knockdown by siRNA.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the activation of the Wnt/β-catenin signaling pathway, downstream LEF/TCF transcriptional activity and the start of EMT process 10 . Many studies have indicated that the WNT signaling pathway can impinge the development of Esophageal squamous cell carcinoma through the EMT pathway [26][27][28][29] . Studies have also shown that PRDM5 can bind to the promoter of TWIST1 to affect its transcriptional activity 10 .…”
Section: Discussionmentioning
confidence: 99%